Environmental impact assessment of southern tehran wastewater treatment plant using life cycle assessment (LCA) - Zeinab Samsami; Ahmad Jonidi Jafari; Mohammad Delnavaz; Azra Naderi; Reza Barati Rashvanlou; Behnam Movassagh Inchehboroun; Emad Dehghanifard (Scientific Reports)
Abstract The population has increased in recent decades, and as a result, the increase in urban wastewater has led to many environmental problems. In this study, the environmental impacts of the Southern Tehran treatment plant were assessed via life cycle assessment (LCA) (SimaPro 9.4.0.2). The information needed for the LCA to be input to the system from the studied treatment plant for 12 months during the year 2022 was gathered from the database and analyzed using the Recepie method. The results of the final effects group showed that in both scenarios, damage to human health, the ecosystem and resource destruction were the most sensitive. A comparison of the final effects of the first and second scenarios revealed that reusing wastewater for irrigation on the Varamin Plain was a more environmentally friendly method, and discharging treated wastewater into receiving water was the worst. Although the use of treated wastewater and digested sludge for agricultural land may save a significant amount of water, it has significant adverse effects on carcinogenic and noncarcinogenic toxicity in humans due to the presence of heavy metals and has a negative effect on global warming.